Turbo Challenge Percepatan UMKM Dengan Pendekatan Coaching Program R-System MCG Rumah Bisnis - Arubina Bangsawan; Anton Trianto; Kemas Welly Angga Permana; Hermansyah Hermansyah; Weny Putry; Liza Novianti (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the national economy, especially in creating employment opportunities and improving community welfare. However, many MSME actors face obstacles in business management, marketing, and adapting to digital technology. To address these challenges, this community service activity aims to accelerate MSME development through the Turbo Challenge program using the R-System coaching approach implemented by MCG Center Rumah Bisnis. The implementation method consists of three main stages: Readiness (enhancing business preparedness), Reinforcement (strengthening managerial and marketing capacity), and Replication (continuous assistance for strategy replication). The activities were carried out with two partners, Rumah Rasa Fitagi and Sarapan Pagi Mama Nisa, through training, technical guidance, and business progress monitoring. The results showed an improvement in partners’ abilities in business planning, digital marketing, and product innovation, which contributed to increased sales and business independence. The conclusion of this activity is that the application of the R-System coaching approach has proven effective in accelerating the transformation and productivity improvement of MSMEs sustainably.